Implementing Digital Technology in Logistics and Supply Chain to Increase Business Competitiveness and Innovation - Gucchi, Anjaka Ray (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
In the context of increasing global competition, Indonesian companies are under pressure to improve their logistics and supply chain systems. Digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), enterprise resource planning (ERP), cloud-based supply chain management (SCM), and blockchain have become strategic necessities rather than optional tools. This study aims to evaluate the effectiveness of digital technology adoption in enhancing efficiency, transparency, speed, and sustainability in logistics, while also examining its impact on competitiveness and innovation. Using a qualitative literature review method, the study synthesizes academic articles, policy documents, and industry reports published in the last five years. The findings demonstrate that IoT and AI improve real-time tracking, demand forecasting, and inventory stability; ERP and cloud-based SCM enhance data integration and visibility; while blockchain significantly increases transparency and supports sustainability through traceability and carbon accounting. Case studies such as Maersk, DHL, and Amazon show that firms integrating these technologies achieve substantial improvements in operational performance, customer trust, and innovative business models. However, successful implementation requires not only technical investments but also organizational readiness, governance frameworks, and stakeholder collaboration. The study concludes that holistic digital transformation in logistics provides a pathway for Indonesian industries to strengthen competitiveness and foster sustainable innovation.